Proceedings of the 15th International Ship and Offshore Structures Congress (Elsevier, 2003)
KEY FEATURES: Provides researchers in Ocean engineering with a thorough review of the latest research in the field Lengthy reports by leading experts A valuable resource for all interested in ocean engineering DESCRIPTION: The International Ship and Offshore Congress (ISSC) is a forum for the exchange of information by experts undertaking and applying marine structural research. These three volumes contain the eight technical committee reports, six Specialist Committee and 2 Special Task Committee reports which were presented for the 15th International Ship and Offshore Structures Congress (ISSC 2004) in San Diego USA, between 11th and 15th August 2003. Volume III will be published in 2004 and is to contain the discussion of the reports, the chairmen's reply, the text of the invited Lecture and the congress report of ISSC 2003
Includes index
Keywords: Marine engineering; Offshore structures; Marine engineering -- Congresses; Offshore structures -- Congresses; Konferenzschrift